ASFV infection induces lipid metabolic disturbances and promotes viral replication - Chu, Xuefei; Ge, Shengqiang; Li, Yingchao; Zhang, Qin; Cui, Xinyu; Zuo, Yuanyuan; Li, Ruihong; Sun, Hongtao; Yin, Lei; Wang, Zhenzhong; Li, Jinming; Xiao, Yihong; et al. (Frontiers in Microbiology, 2025)
IntroductionAfrican swine fever is a highly transmissible and lethal infectious disease caused by the African swine fever virus (ASFV), which has considerably impacted the global swine industry. Lipid metabolism plays a vital role in sustaining lipid and energy homeostasis within cells and influences the viral life cycle.Methods and resultsIn this study, we found that ASFV infection disrupts lipid metabolism in the host. Transcriptomic analysis of cells infected with ASFV revealed that the levels of lipid metabolism significantly changed as the duration of the infection progressed. The intracellular cholesterol levels of the host exhibited a pattern similar to the viral growth curve during the course of infection. Notably, increased cholesterol levels promoted ASFV replication in host cells, whereas inhibition of the cholesterol biosynthesis pathway markedly reduced intracellular ASFV replication.DiscussionThe findings of this study showed that ASFV led to lipid metabolism disturbances to facilitate its replication, which is useful for revealing the mechanism underlying ASFV infection.